Perancangan Ulang Tata Letak Fasilitas Gudang dengan Menggunakan Metode Systematic Layout Planning (SLP) di PT XYZ - Sulistiyono, Wahyu Adji; SZS, Joumil Aidil (Ekonomis: Journal of Economics and Business, 2025)
The purpose of this study is to redesign the layout of warehouse facilities using the systematic layout planning (SLP) method at PT XYZ. The method used in this study is the systematic layout planning (SLP) method, which is a method that has new layout results with minimum distance and OMH (material handling costs) results. The results of the study found that the initial layout distance of the storage rack to the pharmacist's room was 624,625m and in the proposed layout it became 416,139m, then also in the initial layout the total moment of storage rack movement to the pharmacist's room was 5833,306m/day and in the proposed layout it became 3439,759m/day. In the initial layout the total material handling cost (OMH) of the storage rack to the pharmacist's room was Rp. 39,793,333.3 and in the proposed layout it became Rp. 2,750,154.7.